Tao and Trinity: Notes on Self-Reference and the Unity of Opposites in Philosophy - Austin, S. author. aut Link
X, 130 p. 2 illus.
Keywords: The Chinese Tao and the Western Trinity have a fundamental unity of theme: the unity of opposites. Both are connected with problems as broad and diverse as how to describe the entire universe, how a system can talk about itself, the relationship between symbols and realities, and the nature of signs and sacraments.